Perancangan Sistem Informasi Monitoring Kepegawaian Berbasis Web Di Dinas Koperasi Dan UKM Kota Medan - Barutu, Atika Goretti; Susilawati, Susilawati (Jurnal Ilmiah Teknik Informatika & Elektro (JITEK), 2024)
The need for the use of information systems is currently felt by the Medan city Cooperative and ukm Office. Especially the use of information systems with the aim of assisting operational activities in terms of monitoring staffing, namely leave, promotions and employeest retiretment. The staffing monitoring system at the Cooperatives and UKM Office in Medan City has not been computerized. Through this practical work report, the authors propose to design a web-based staffing monitoring system through several stages, namely, data collection which includes interviews and practical work, software design including needs analysis, and system design. The result of thisf practical work is the design of a web-based staffing at the Cooperatives UKM Office in Medan City.